Beliefs, knowledge and attitudes of community-dwelling Greek elders towards influenza and pneumococcal vaccination - Raftopoulos, Vasilios (My University, 2007)
Background: Influenza is a major cause of mortality and morbidity in the elderly. Objective: To explore the knowledge, attitudes, and beliefs of community-dwelling Greek elders towards influenza and pneumococcal vaccination. Method: Content analysis methodology was used to analyse three focus group interviews (n=22). The theoretical framework of the Health Belief Model was used. Results: Two-thirds of the elderly participants have received flu vaccine last year. The main motives and barriers that explain elders' behaviour were: having routine access to medical care; the recommendation of health care professionals; beliefs about the benefits of influenza vaccination; having a relative who delivered the vaccine; being less than 75 years old; having unpleasant reactions in the past; lack of adequate information about the side effects of influenza vaccine; and vaccine shortages. Conclusions: Availability of sufficient vaccines and health education programs are needed to increase the uptake of influenza and pneumococcal vaccination.
Keywords: Influenza vaccination; Pneumococcal vaccination; Elderly; Flu; Vaccine shortage; Vaccine coverage